O melhor da arte barroca - Rosario Camacho, Cristóbal Belda Navarro, María Isabel Álvaro Zamora (G & Z)
20.º vol.: Rosario Camacho, 47 p.; 21.º vol.:Cristóbal Belda Navarro, 47 p.; 22.º vol.: María Isabel Álvaro Zamora, 47 p.